MSH6 germline mutations leading to Lynch syndrome-associated cholangiocarcinoma: a case report - Zhang, Zheng; Ma, Subo; Li, Shixing; Chen, Zhengfu; Song, Runda; Wang, Zhanpeng (Frontiers in Oncology, 2024)
Lynch syndrome, a hereditary cancer susceptibility syndrome, arises from pathogenic mutations in mismatch repair genes. This syndrome is strongly linked to colorectal and endometrial cancers, as well as an elevated risk for other cancers such as gastric, ovarian, renal pelvis/ureter, and prostate. Notably, Lynch syndrome is rarely associated with cholangiocarcinoma (CCA). In this case study, we present a unique instance of Lynch syndrome-related CCA resulting from a singular MSH6 mutation. Notably, our findings reveal discrepancies between immunohistochemistry (IHC) and microsatellite stability results compared to genetic testing outcomes. This discrepancy underscores the limitations of solely relying on IHC analysis and microsatellite stability testing for the detection of hereditary tumors, emphasizing the crucial role of genetic testing in such cases. This insight enhances our comprehension of the mechanisms involved in cancer development and underscores the significance of thorough analysis integrating immunohistochemistry and genetic testing for diagnosing Lynch syndrome-related cancers.